2020
DOI: 10.1002/jobm.201900520
|View full text |Cite
|
Sign up to set email alerts
|

Influence of selenium yeast on the growth, selenium uptake and mineral composition of Coriolus versicolor mushroom

Abstract: The ability of Coriolus versicolor medicinal mushroom to grow and accumulate selenium during submerged cultivation in a selenium‐fortified medium is examined in this paper. For selenium supplementation, commercial selenium yeast was used. Control, nonenriched sample and reference cultures cultivated in the medium enriched with commercial yeast Saccharomyces cerevisiae were also prepared. The mushroom demonstrated a high ability to accumulate selenium from the added source (around 970 and 1,300 µg/g of dry myce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…The bioaccumulation of Se by various microorganisms has been widely studied by many authors. As reported by Miletić et al [45], the medicinal fungus Coriolus versicolor grown in medium supplemented with 10 and 20 mg Se/L could accumulate 970 and 1300 µg/g of Se, respectively. Ullah et al [46] showed that the probiotic bacteria Bacillus subtilis BSN313 grown in Se-enriched medium at the dose of 12 µg/mL could bind 2.123 µg Se/g.…”
Section: Se Bioaccumulationsupporting
confidence: 59%
“…The bioaccumulation of Se by various microorganisms has been widely studied by many authors. As reported by Miletić et al [45], the medicinal fungus Coriolus versicolor grown in medium supplemented with 10 and 20 mg Se/L could accumulate 970 and 1300 µg/g of Se, respectively. Ullah et al [46] showed that the probiotic bacteria Bacillus subtilis BSN313 grown in Se-enriched medium at the dose of 12 µg/mL could bind 2.123 µg Se/g.…”
Section: Se Bioaccumulationsupporting
confidence: 59%
“…The easily digestible proteins of mushrooms are determined as the main carrier of the mushroom’s nutritional value because they could provide all essential amino acid requirements [ 68 ]. Apart from the nutritional value, there are reports about bioactive proteins and peptides demonstrating pharmacological potential [ 68 , 85 , 86 , 87 ]. The protein content of the wild fruiting body and mycelium biomass obtained through submerged cultivation usually varies.…”
Section: Resultsmentioning
confidence: 99%
“…The studies outlined above generally show that HSA/Se NPs have good biosafety, although some reports indicate that Se has therapeutic effects in PD. 32 Furthermore, the range between therapeutic and toxic doses is narrow and cannot effectively reach the midbrain lesion area. Therefore, this study compared the therapeutic effects of HSA/Se NPs, nano-Se, and Selenious yeast in subacute PD model mice.…”
Section: Therapeutic Effects Of Hsa/se Nps and Other Sementioning
confidence: 99%